Vibration Analysis by the Gabor Transform Method - Jaroslav Smutny; Daniela Vukusicova; Viktor Nohal; Herbert Seelmann (Communications - Scientific letters of the University of Zilina, 2017)
This paper deals with description and application of the Gabor transform for vibration analysis. This transform belongs to the group of linear time-frequency processes. Thanks to its properties, it may be successfully used in the area of non-stationary and transitional signals describing various natural processes. Use for analysis of vibrations caused by railway transport represents quite an interesting application area of this transform. This paper contains mathematical analysis of the transform, a case study and practical experience obtained, as well as recommendations for its practical use.